The effects of anesthesia methods and anesthetics on postoperative delirium in the elderly patients: A systematic review and network meta-analysis - Zhuang, Xuhui; He, Yuewen; Liu, Yurui; Li, Jingjing; Ma, Wuhua (Frontiers in Aging Neuroscience, 2022)
Study objective: Postoperative delirium (POD) is one of the serious postoperative complications in elderly patients, which is always related to the long-term mortality. Anesthesia is often considered a risk factor for POD. This systematic review and network meta-analysis (NMA) aimed to assess the impact of different anesthesia methods and anesthetics on POD. Measurements: We searched for studies published in PubMed, Embase, Web of science, Scopus and Cochrane Library (CENTRAL) from inception to March 18, 2022. RevMan 5.3 and CINeMA 2.0.0 was used to assess risk of bias and confidence. Data analysis using STATA 17.0 and R 4.1.2. STATA 17.0 was used to calculate the surface under the cumulative ranking curve (SUCRA) and provide network plots with CINeMA 2.0.0. NMA was performed with R 4.1.2 software gemtc packages in RStudio. Main results: This NMA included 19 RCTs with 5406 patients. In the pairwise meta-analysis results, only regional anesthesia (RA) with general anesthesia (GA) vs. GA (Log OR: -1.08; 95% CI: -1.54, -0.63) were statistically different in POD incidence. In the NMA results, there was no statistical difference between anesthesia methods, and psoas compartment block (PCB) with bupivacaine was superior to the desflurane, propofol, sevoflurane, spinal anesthesia with bupivacaine of POD occurrence. Conclusion: Our study indicated that RA and GA had no significant effect on POD, and there was no difference between anesthesia methods. Pairwise meta-analysis showed that, except for RA with GA vs. GA, the rest of the results were not statistically different. Besides, PCB with bupivacaine may benefit to reduce POD incidence.